Istota, funkcjonowanie i kierunki rozwoju usług private banking w Polsce - Bednarska-Olejniczak, Dorota (The Functioning and Directions of Development of Private Banking in Poland, 2007)
For many years private banking trade was identified with Switzerland, Great Britain, United States of America and other wealthy and economically developed countries. In fact, private banking has been present in Poland for over 10 years. The main goal of this article is a presentation of private banking services currently existing in our country and characteristics of Polish private banking trade clients. The paper also presents hitherto existing Polish private banking and forecasts possible directions of its evolution. It also indicates possible barriers in the course of private banking services development in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 167-175